The historical criminal statistics of Finland 1842–2015 – a systematic comparison to Sweden - Vuorela, Miikka (International journal of comparative and applied criminal justice, 2018)
The purpose of the article is to provide an overview to the trends in crime and crime control in Finland and Sweden during the past 150 years, systematically comparing the two countries. The secondary objective of the study is to introduce a Nordic data collection project aiming to compile coherent comparative criminal justice time series from the early nineteenth century to the present, and to present the first collection of data, the Finnish justice statistics 1842-2015. The study examines the long-term development of homicide, assault, rape, defamation, prison population, and penal severity. Historical statistics provide opportunities to examine the crime trends and the society’s responses to them keeping in mind that the statistics do not necessarily reflect changes in total criminality. As such, the study does not provide conclusive explanations on the development of crime and punishment but rather opens new questions to be answered in future research.